Diet and Behavior of Macaca fascicularis for Ecotourism Contributing on Pengsong Area - M. Yamin; Dadi Setiadi; Khairuddin Khairuddin (Jurnal Biologi Tropis, 2021)
Mount Pengsong is a mountainous ecotourism area with beautiful natural scenery and interesting biodiversity, including the presence of Macaca fascicularis populations. Type of food Macaca fascicularis in the tourist area of Mount Pengsong is not yet known, including itÃ¢â¬â¢s carrying capacity for population numbers. This study aims to determine the types of plants eaten and the types of food provided by visitors as well as the nutritional content of food consumed by monkeys in the area and the behavior of Macaca fascicularis as a management basis to support ecotourism in Mount Pengsong.ÃÂ  Data were collected using the "broad survey and line transect" method in the morning, afternoon and evening. Food data taken includes sources of food, drink, weather, temperature, humidity, humidity, altitude from sea level, and human activities around. The MacacaÃÂ  fascicularis behavior data studied were daily activities, time to eat, play, rest, breed, population structure, population disturbance, social patterns (solitary / pair / group) and home range. The result is a monkey diet in the form of plants available around the tourist area as many as 23 species, 5 types of animals, 10 types of plants produced in agricultural areas and nine Types of food provided by visitors. Nutritional needs and elements can be fulfilled from available food sources and it will be more perfect by obtaining other food sources provided by visitors. Macaca fascicularis consumes a lot of plant species and is very dependent on the availability of food in its environment, the food given by visitors is liked by monkeys and provides good nutritional value. The population of Macaca fascicularis in the tourist area of Mount Pengsong was 83 individuals, 83 of whom were recorded from 9 (ÃÂ± 11%) adult males, 29 (ÃÂ± 35%) adult females and 45 (ÃÂ± 54%) juveniles and children. Daily activities of Macaca fascicularis were recorded as moving (35%), grooming (25%), playing (15%), inactive (10%), eating (6.8%), agonistic (3.6%), sleeping (2.3%), mating (0.9 %), and have a voice (0.8%).